2000
DOI: 10.1016/s1385-1101(00)00014-9
|View full text |Cite
|
Sign up to set email alerts
|

Architecture, ecology and biogeochemistry of Phaeocystis colonies

Abstract: This paper discusses structure and function of the Phaeocystis colony skin, and relates them to the specific impact of Phaeocystis colonies on ecology and biogeochemistry. The potential advantage of the recently discovered tough skin around the colonies of Phaeocystis globosa is discussed in context with the metabolic costs of this structure, and compared to potential functions of structures around other phytoplankton. It is further proposed that mainly small, fast-growing pathogens and predators will be deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 53 publications
1
51
1
1
Order By: Relevance
“…This suggests that at high growth rate, Phaeocystis could build more colonies with fewer cells, which may further reduce grazing mortality . Because Phaeocystis solitary cells are more readily consumed by grazers relative to colonies ), our results suggest that P. globosa might experience increased grazing pressure at higher temperature, and combined with the near-0 sinking rates of solitary cells, could result in a reduced Phaeocystis carbon flux to the sediments (Hamm & Rousseau 2003, Reigstad & Wassmann 2007 and increased POC retention within the pelagic food web (Hamm 2000). Reduced colony formation at higher temperature would also reduce the amount of mucilage production and bacterial activities that are supported by it (Becquevort et al 1998, Rousseau et al 2000.…”
Section: Solitary Vs Colonial Formsmentioning
confidence: 84%
“…This suggests that at high growth rate, Phaeocystis could build more colonies with fewer cells, which may further reduce grazing mortality . Because Phaeocystis solitary cells are more readily consumed by grazers relative to colonies ), our results suggest that P. globosa might experience increased grazing pressure at higher temperature, and combined with the near-0 sinking rates of solitary cells, could result in a reduced Phaeocystis carbon flux to the sediments (Hamm & Rousseau 2003, Reigstad & Wassmann 2007 and increased POC retention within the pelagic food web (Hamm 2000). Reduced colony formation at higher temperature would also reduce the amount of mucilage production and bacterial activities that are supported by it (Becquevort et al 1998, Rousseau et al 2000.…”
Section: Solitary Vs Colonial Formsmentioning
confidence: 84%
“…1). Microscopic and chemical analyses have found that Phaeocystis colonies are filled with a mucilaginous matrix surrounded by a thin but strong hydrophobic skin (Hamm, 2000;Hamm et al, 1999). Once formed, cells typically associate with this outer layer of the colony .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, not only does the colony increase the size of Phaeocystis by several orders of magnitude, but the extracellular matrix material also constitutes the majority of measured algal (carbon) biomass (Rousseau et al, 1990). The colonial form of Phaeocystis has been suggested as a defense mechanism against grazers (Hamm et al, 1999), a means to sequester micronutrients such as iron and manganese (Lubbers et al, 1990;Schoemann et al, 2001), a means of protection from pathogens (Hamm, 2000;Jacobsen et al, 2007), and as a microbiome vitamin B 12 source (Bertrand et al, 2007). Colony formation of Phaeocystis species, including P. antarctica and P. globosa, has been linked to numerous physiological triggers including the synergistic effects of iron and irradiance (Feng et al, 2010), grazer-induced chemical cues (Long et al, 2007), phosphate concentrations (Riegman et al, 1992), and the presence of different nitrogen species (Riegman and van Boekel, 1996;Smith et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this variability on fisheries and local community structure can be considerable and could be generated by grazer-induced transformations between the two primary forms of most Phaeocystis species: solitary cells of 4-6 m and colonies that can reach up to 30,000 m in diameter (7). Although these transformations can represent a biovolume change of Ͼ10 orders of magnitude and may affect bloom initiation, the cues affecting colony formation are inadequately understood (8,9). Given that size-specific feeding is common in planktonic consumers (10,11), detecting the threat of grazing and responding by switching to a less susceptible phenotype could decrease losses of Phaeocystis to consumers as do the induced morphological and chemical defenses of some terrestrial plants, seaweeds, and freshwater zooplankton (12)(13)(14).…”
mentioning
confidence: 99%